2016
DOI: 10.1016/j.ymgmr.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Successful intrauterine treatment of a patient with cobalamin C defect

Abstract: Cobalamin C (cblC) defect is an inherited autosomal recessive disorder that affects cobalamin metabolism. Patients are treated with hydroxycobalamin to ameliorate the clinical features of early-onset disease and prevent clinical symptoms in late-onset disease. Here we describe a patient in whom prenatal maternal treatment with 30 mg/week hydroxycobalamin and 5 mg/day folic acid from week 15 of pregnancy prevented disease manifestation in a girl who is now 11 years old with normal IQ and only mild ophthalmic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This has prompted therapeutic trials of hydroxycobalamin in fetuses known to have the disorder. 20,21 In our cohort, the lowest recorded methionine and highest homocysteine values were correlated with neurodevelopmental outcomes. These extreme values generally occurred in the neonatal period prior to therapy initiation and therefore may reflect the degree of metabolic derangement in utero.…”
Section: Discussionmentioning
confidence: 53%
“…This has prompted therapeutic trials of hydroxycobalamin in fetuses known to have the disorder. 20,21 In our cohort, the lowest recorded methionine and highest homocysteine values were correlated with neurodevelopmental outcomes. These extreme values generally occurred in the neonatal period prior to therapy initiation and therefore may reflect the degree of metabolic derangement in utero.…”
Section: Discussionmentioning
confidence: 53%
“…For cblC disease, Trefz et al (2016) report a favourable outcome of a pregnancy with an affected fetus (sibling to a severely affected child) after treatment of the mother with high-dose OHCbl (30 mg/week) and 5 mg/day folic acid from week 15 of pregnancy. Prenatal treatment with lower OHCbl doses resulted in biochemical improvement.…”
Section: The Effects Of Treatment On Clinical Outcomementioning
confidence: 99%
“…Intrauterine therapy is used to treat fetuses with MMA. Trefz et al 31 reported a patient with MMA in whom prenatal maternal treatment from week 15 of pregnancy prevented disease manifestation in a girl who is currently 11 years old with a normal IQ. However, we did not offer prenatal B12 therapy to the mother of family 7, and the pregnant woman chose to terminate the pregnancy.…”
Section: Discussionmentioning
confidence: 99%